2020
DOI: 10.21203/rs.2.12213/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Global Health Capstone: An Innovative Educational Approach in a Competency-Based Curriculum for Medical Students

Abstract: Background Global health educational programs for medical and public health professionals have

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Given the major global changes and the increasing interest in global health, there is a growing need for integrated and formalized programming that allows students to develop relevant skills as well as the ability to apply theoretical concepts in high-impact global health initiatives. Several examples demonstrate how a structured global health capstone is a method for teaching global health skills and preparing students for careers as global health professionals and leaders [17].…”
Section: Attitude and DI Culties Of Students Undergoing Training In R...mentioning
confidence: 99%
“…Given the major global changes and the increasing interest in global health, there is a growing need for integrated and formalized programming that allows students to develop relevant skills as well as the ability to apply theoretical concepts in high-impact global health initiatives. Several examples demonstrate how a structured global health capstone is a method for teaching global health skills and preparing students for careers as global health professionals and leaders [17].…”
Section: Attitude and DI Culties Of Students Undergoing Training In R...mentioning
confidence: 99%
“…[3][4][5][6] As part of a movement toward more structured and intentional global health education, global health educators have invested in defining competencies in global health. [7][8][9] However, there remains a lack of consensus on the desired global health competencies and how to assess the acquisition of these competencies. [10][11][12][13][14][15] We found that promoting reflective writing during global clinical rotations (GCRs) can provide a means to illustrate medical student learning consistent with the eight American Association of Medical College (AAMC) physician competency domains.…”
Section: Introductionmentioning
confidence: 99%